1982
DOI: 10.1007/bf01315175
|View full text |Cite
|
Sign up to set email alerts
|

Electron microscopic studies of bovine viral diarrhea virus in tissues of diseased calves and in cell cultures

Abstract: Pathomorphological studies by electron microscopy (EM) were carried out on the intestines and lymphoid tissues, the buffy coat cells and cultured lymphocytes from calves suffering from mucosal disease (MD). This led to the detection of particles, 45--55 nm in diameter, within characteristic vesicular structures. As these findings coincided with the isolation of bovine viral diarrhea virus (BVDV) from the same tissues and demonstration of BVDV-antigen by immunocytochemical techniques in corresponding samples, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

1985
1985
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…This range contrasts with the size reported here of 46 nm which is in close agreement with the diameter of 50 nm reported by Ritchie & Fernelius (1969), Chasey & Roeder (1981) and Ohmann & Bloch (1982). Chasey & Roeder (1981) reported the presence of tubules in infected cells but unlike the present study did not observe virus particles within them.…”
Section: Ultrastructure Of Bd V-and B Vd V-infected Cellssupporting
confidence: 88%
See 1 more Smart Citation
“…This range contrasts with the size reported here of 46 nm which is in close agreement with the diameter of 50 nm reported by Ritchie & Fernelius (1969), Chasey & Roeder (1981) and Ohmann & Bloch (1982). Chasey & Roeder (1981) reported the presence of tubules in infected cells but unlike the present study did not observe virus particles within them.…”
Section: Ultrastructure Of Bd V-and B Vd V-infected Cellssupporting
confidence: 88%
“…One previous study of BDV and BVDV in tissue sections has been made (Scott et al, 1977) but later studies of BVDV from the same laboratory by Chasey & Roeder (1981) concluded that the particles described were non-viral. Other studies of BVDV in thin sections have been made by Ritchie & Fernelius (1969) and Ohmann & Bloch (1982) who described BVDV virus as spherical particles approximately 50 nm in diameter. Most studies of BVDV have utilized suspensions of virus and negative staining (Hafez et al, 1968;Maess & Retzko, 1970;Horzinek et al, 1971 ;Stott et al, 1974;Chu & Zee, 1984), and have variously reported the virus as roughly spherical and from 30 to 100 nm or more in diameter.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported by others that pestivirions are released from large vacuoles in large numbers and/or aggregates (21,40). However, the described vacuoles may represent MVBs, and the observed particles may represent ILVs instead of virions, especially since the authors observed particles with identical morphology in vacuoles of uninfected cells.…”
Section: Discussionmentioning
confidence: 48%
“…The molecular weights of the structural proteins are: E! and E2, (50-59) x I03; E3 (when present), 10 x 103; C, (30)(31)(32)(33)(34) x 103 [6]. The gene sequence is 5'nsPl-nsP2-nsP3-nsP4-C-E3-E2-El-3', con firmed from the complete nucleotide se quence of Sindbis virus RNA [9].…”
mentioning
confidence: 99%
“…Very little informa tion is available on their replication; only a single species of virus-specific RNA [relative molecular mass (Mr) about 3 x 10''] with anomalous sedimentation behavior and un usual RNase resistance was identified in cells infected with mucosal disease virus [30]. Vir ions accumulate within the cisternae of mem branous organelles [4,11,12,31]. The three species in the genus show antigenic relation ships by immunodiffusion, antibody neutral ization, and fluorescence [11,12).…”
mentioning
confidence: 99%